Does tolerance to ethanol-induced ataxia explain the sensitized response to ethanol? - Reed, Cheryl; Phillips, Tamara J. (Frontiers in Psychiatry, 2024)
Under conditions of repeated exposure to ethanol, a sensitized locomotor stimulant response develops in some strains of mice. It has been hypothesized that the sensitized response is a consequence of tolerance development to the sedative/incoordinating effects of ethanol. Conversely, ethanol-induced sensitization and tolerance may be independent effects of repeated ethanol exposure. A published study in C57BL/6J by DBA/2J recombinant inbred strains concluded that the two phenomena are not genetically related and thus perhaps mechanistically distinct. To extend evaluation beyond the genetic variance found in C57BL/6J and DBA/2J mice and examine phenotypic associations, we simultaneously measured ethanol-induced sensitization and tolerance in a genetically diverse panel of 15 standard inbred mouse strains and a genetically heterogeneous stock that was produced by the intercrossing of eight inbred mouse strains. Changes in activity counts and ataxia ratio across repeated ethanol treatments indexed sensitization and tolerance, respectively. Photocell beam breaks provided the measure of activity, and foot slip errors corrected for activity in a grid test provided a measure of coordination. The results were strain and individual dependent. The genetic correlation between magnitude of sensitization and tolerance was not significant in the panel of inbred strains, but when individual data were correlated, without regard to strain, there was a significant correlation. This relationship was also significant in the genetically heterogeneous population of mice. However, magnitude of tolerance explained only 10% of the variance in sensitization among individuals of the inbred strain population, whereas it explained 44% of the variance among individuals of the eight-strain cross. When repeated exposures to ethanol were disassociated from the test apparatus, this relationship in the eight-strain cross disappeared. Furthermore, days to peak sensitization and tolerance across days did not perfectly mirror each other. Overall, our data do not support shared genetic mechanisms in sensitization and tolerance development but suggest a partial relationship among individuals that could be related to drug–environment associations.